LncRNA-AC009948.5 promotes invasion and metastasis of lung adenocarcinoma by binding to miR-186-5p - Bai, Jun; Li, Hongli; Chen, Xinlu; Chen, Lin; Hu, Yaqiong; Liu, Lu; Zhao, Yanqiao; Zuo, Wei; Zhang, Baogang; Yin, Chonggao (Frontiers in Oncology, 2022)
Abstract: Background: Long non-coding RNAs (LncRNAs) has been confirmed to play a crucial role in the development and progression of various cancer types. Here we evaluated the expression profiles of LncRNAs in Lung adenocarcinoma (LUAD) tissues and identified a novel LncRNA, termed LncRNA-AC009948.5. However, the role and potential molecular mechanisms of this novel LncRNA in LUAD carcinogenesis is unknown. Methods: Regarding the public databases and based on integrating bioinformatics analyses, we determined whether LncRNA-AC009948.5 exerts its oncogenic functions via sponging miR-186-5p in LUAD. Furthermore, we determined whether NCAPG2 was a downstream target of miR-186-5p. Moreover, the expression level and biological function of LncRNA-AC009948.5 in LUAD were determined by qRT-PCR, cell apoptosis, Edu, transwell, wound healing and western blot assays. Besides, xenograft mice were established for validation. We explored the expression of LncRNA-AC009948.5 and its roles in the prognosis of LUAD. Results: LncRNA expression microarray data indicate that LncRNA-AC009948.5 is upregulated in LUAD samples. The present study confirmed the downregulation of LncRNA-AC009948.5 in LUAD tissues and cells. Encreased expression of LncRNA-AC009948.5 was correlated with tumor size, lymph nodes, distant metastasis and histological grade, and poor prognosis.LncRNA-AC009948.5 knockdown significantly inhibited cell proliferation, migration, and invasion in vitro, as well as tumorigenesis and metastasis in vivo. Conversely, LncRNA-AC009948.5 upregulated had opposite effects. Mechanistically, we elucidated that LncRNA-AC009948.5 could directly bind to miR-186-5p and subsequently suppress expression of the target gene of NCAPG2. Conclusions: LncRNA-AC009948.5 promotes lung adenocarcinoma cells metastasis via the miR-186-5p/NCAPG2 axis and activation of the EMT process. Which may serve as potential targets for the treatment of LUAD in the future.